A Partnership Pattern of the Tengger Indigenous People in Management of the Bromo Tengger Semeru National Park - Shrimanti Indira Pratiwi; I Nyoman Nurjaya; Imam Koeswahyono; Djumikasih Djumikasih (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The Tengger indigenous people are a traditional entity spread across Bromo Tengger Semeru National Park. The Tengger indigenous people have inhabited Tengger mountains since the time of Majapahit kingdom. Indonesian government has designated Tengger mountain area as the Bromo Tengger Semeru National Park. The aim of this research is to determine a partnership pattern of Tengger indigenous people in collaborative management with the Bromo Tengger Semeru National Park office because if examined from a judicial perspective, costumary law has been marginalized by enactment of state law. The type of this research used a Socio-Legal Research with a legal anthropology approach. The main data source was obtained from in-depht interview with Gatekeepers and informants. The research findings show that there has been no true participation of the Tengger indigenous people in managing National Park area because the national park office make many policy regulations and determine area zoning unilaterally without considering the local wisdom that is owned by the Tengger indigenous people which has been passed down across generations for thousand of years. The Bromo Tengger Semeru National Park only uses an approach based on a spectrum of ecological sensitivity to maintain conservation area and determine the zones area. There is a need for a collaborative management pattern together with the Tengger indigenous people to achieve an ecologically sustainable conservation area. Collaborative management with the society also prevents the domino effect of ecological damage due to the high number of tourist both local and foreign, visiting the national park.